Linking Carbonate Facies to Stylolite Distribution of Middle Jurassic Limestone, Onshore Abu Dhabi Oil Field - Prahastomi, Mochammad; Morad, Sadoon; Al Suwaidi, Aisha; Ali, Mohammed; Muljana, Budi; Adlan, Ryandi (Institut Teknologi Adhi Tama Surabaya, 2025)
This study examines the relationship between facies and stylolitization in the Upper Araej Member carbonates of onshore Abu Dhabi. Analysis of core and thin sections identified four facies: wispy-laminated skeletal wackestone (F-1), peloidal skeletal mud-dominated packstone (F-2), coated-grain skeletal grainstone (F-3), and peloidal skeletal floatstone (F-4), deposited across a shallow carbonate ramp. Stylolites were described and measured for vertical offset amplitude to assess facies dependence. Results show facies-related tendencies in stylolite amplitude and morphology. Mud-supported facies (especially floatstones and wackestones) tend to display higher variability, with floatstones reaching amplitudes of up to 20 mm, whereas grainstones may also contain isolated high-amplitude stylolites (up to 14 mm). Packstones and wackestones, by contrast, rarely exceed 10-13 mm. Boxplots highlight greater variability in mud-rich facies, whereas grainstones exhibit narrower distributions. Statistical testing (ANOVA, p = 0.109; Kruskal–Wallis, H = 3.38, p = 0.34) indicates no statistically significant differences in mean stylolite amplitude across facies, although descriptive data reveal trends in variability and extremity. Jagged stylolites occur in both mud-rich and grain-supported facies, whereas wispy seams are strongly associated with micrite-rich facies and are largely absent in grainstones. Stylolites in these carbonates may act as both vertical barriers and localized porosity enhancers. Their facies-associated occurrence emphasizes the need to integrate stylolitization into reservoir models to better predict connectivity, compartmentalization, and flow behavior in Middle Jurassic carbonates.